AMBITIONS AS THE EFFECT OF CHILDHOOD EXPERIENCE IN E.L. JAMES'S FIFTY SHADES OF GREY - L. Dyah Purwita Wardani SWW; Nurul Islamiyah; Imam Basuki (UNEJ e-Proceeding, 2020)
This article aims to analyze the effect of the male character childhood in E.L. James's Fifty Shades of Grey By using psychological approach to analyze the fictitious character and the creative process of the author. Theory of interpretation of dream by Sigmund Freud is applied in order to explain the causes of ambition done by Christian Grey. Grey’s ambition is caused by the desire to revenge from his trauma in his childhood. There are three factors that make the character ambitious: The first is when Grey uses his violence (BDSM) to dominate his partner. The second is when Grey want become rich and popular man. The last is Grey’s heart emptiness after a woman he loved left him. The first problem is in the field of abnormal psychology in order to differentiate abnormal from normal behavior. In short, Grey's ambitions are caused by a traumatic condition when he was a child. E.L. James explains a sexual lifestyle which is called BDSM (Bondage/ Disipline, Dominance/ Submissive, Sadism/ Masochism). By exposing this lifestyle in her novel, the author wants to shows that BDSM is not an equal relationship between man and woman. Keywords: ambition, BDSM, psychology, relationship